Effective teaching - Dunne, Richard; Wragg, Ted. (London ; New York : Routledge, 1994)
What is effective teaching? Improving personal competence. Understanding how children learn. Classroom organisation and management. Instructional design. Whole-school issues.
Keywords: Education; Primary school teaching; Primary school teaching; Primary school teaching -- Great Britain